Pembatasan Usia Minimal Perkawinan dalam Hukum Keluarga Islam Studi Komparasi Indonesia dan Yordania - M. Syarfi Iqbal; Moh. Asyiq Amrulloh (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The minimum age limit for marriage in Islamic Family Law is a provision that regulates the minimum age limit that must be met by individuals before legally entering into a marriage according to the principles of Islamic law. This is intended to protect the parties involved and ensure the physical, mental and emotional maturity of prospective partners before entering into marriage. This research uses a qualitative descriptive approach using literature study methods to investigate differences in minimum age restrictions for marriage between Islamic law and state policy. Data collection was carried out through direct surveys and literature searches from trusted sources, including international journals, books and e-books. The literature study method involves three essential steps: Literature Inventory, Literature Description, and Literature Comparison. The research focus is focused on analyzing laws regarding minimum age limits for marriage in various countries, with an emphasis on comparisons between Islamic legal views and implementation of state policies. The research findings produced several conclusions, including: 1) Differences in approach between Islamic law which does not set a minimum age limit and state policies such as Indonesia (19 years) and Jordan (18 years); 2) Limiting the age of marriage as an effort to protect and mature individuals in living a married life; 3) Rearranged minimum standardization divergence to prevent misuse; 4) Marriage as an institution with noble purposes, interpreted by Islamic law and adopted by the state taking into account local, social and cultural aspects.